1998
DOI: 10.1063/1.367721
|View full text |Cite
|
Sign up to set email alerts
|

Role of interfacial uncompensated antiferromagnetic spins in unidirectional anisotropy in Ni81Fe19/CoO bilayers (invited)

Abstract: The uncompensated spins on the surfaces of antiferromagnetic CoO films exhibit a thermoremanent magnetization after field cooling from T>TN that has the same temperature dependence as the exchange field of Ni81Fe19/CoO bilayers after field cooling. This suggests that these interfacial uncompensated spins are responsible for unidirectional anisotropy. A model based on a calculation of the density of these interfacial uncompensated spins predicts the correct magnitude of the exchange field, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 11 publications
0
42
0
2
Order By: Relevance
“…This is because both polycrystalline and epitaxial antiferromagnetic films are very sensitive to spin texture faults (due to roughness, atomic stacking faults, etc.) that create randomly spread disordered magnetic phases ( Takano et al, 1997;Baltz, Rodmacq et al, 2010;Lhoutellier et al, 2015). In addition, lateral finite-size effects on antiferromagnetic materials are not straightforward: lateral size reduction affects the antiferromagnetic domain size, and it also introduces boundaries.…”
Section: Spatial Variability Of Magnetic Propertiesmentioning
confidence: 99%
“…This is because both polycrystalline and epitaxial antiferromagnetic films are very sensitive to spin texture faults (due to roughness, atomic stacking faults, etc.) that create randomly spread disordered magnetic phases ( Takano et al, 1997;Baltz, Rodmacq et al, 2010;Lhoutellier et al, 2015). In addition, lateral finite-size effects on antiferromagnetic materials are not straightforward: lateral size reduction affects the antiferromagnetic domain size, and it also introduces boundaries.…”
Section: Spatial Variability Of Magnetic Propertiesmentioning
confidence: 99%
“…However, it seems inconsistent with the generally accepted dependence of exchange coupling strength that goes inversely proportional to D [11,12]. This apparent inconsistency will be understood as the effect of the increase of the total contact area of relatively large IrMn grains with the increase in the Cu-thickness, due to the increase of both the number and size of IrMn grains directly coupled with the FeCo layer, as is observed in the TEM micrographs.…”
Section: Article In Pressmentioning
confidence: 69%
“…Thus, a few atomic layers of FeMn at the seed NiFe/FeMn interface (the transitional layers) may have a parallel net spin ordering in the direction of the applied field and NiFe layer that provide the net spin moments required for exchange coupling and bias. It has been observed that only 1% of the total spins at the ideal interface need to be aligned in the direction of ferromagnet spins to produce the observed exchange bias [6]. This is attained in the (1 1 1) plane of the FeMn grown on the textured bottom NiFe interface.…”
Section: Article In Pressmentioning
confidence: 95%